The Implementation of The Negativa Non Sunt Probanda Principle in Indonesian Civil Litigation: An Analysis of Banten High Court Decision Number 109/PDT/2022/PT BTN - Muhammad Sulhan; Umar Haris Sanjaya (Jurnal Hukum Replik, 2026)
In the Indonesian legal system, civil procedural law pays great attention to the principles underlying decision making by judges in civil cases. One of the principles regulated in civil law is the principle of negativa non sunt probanda, which is often understood as the principle that states that "what is not proven is what does not need to be proven." This principle plays an important role in regulating the burden of proof in a civil dispute. In this thesis, the author will discuss the application of this principle in private lawsuits, with a case study of Civil Case Decision Number: 109/PDT/2022/PT BTN. The formulation of the research problem is how the implementation of the Negative Non Sunt Probanda Principle and it is possible to use Negative Non Sunt Probanda principle be used in private in Implementation as a jurisdiction. The research method used is normative legal research, including the case approach and the statute approach. Data sources were obtained from primary data include th 1945 Constitution of the Republic of Indonesia, Civil Code, HIR, RBg, Rv, and others. The secondary data can be in the form of explanations and/or understanding of scientific writing thoughts, scientific publications, and research related to the writing of this law. The results of this research show that the application of the principle of Negativa Non Sunt Probanda in the context of civil law, as seen in the decision in case number 109/PDT/2022/PT BTN, shows that the court firmly emphasizes that the burden of proof lies on the party making the claim. The principle of Negativa Non Sunt Probanda, which means "the negative does not need to be proven," has an important role in the application of civil law, especially in the context of litigation. Keywords: Negative Non Sunt Probanda Principle, Civil Case, Court Decisions